Yield rate in the Warsaw office market and its determinants. Further studies - Nowak, Krzysztof (Publishing House of Wroclaw University of Economics and Business, 2024)
This article is a continuation and extension of a previous study which, to the best of the author’s knowledge, was the first scientific attempt to identify determinants of the yield rate in the Warsaw office market. The paper is based on the Gordon growth model. In this approach, the yield rate of buildings offering office space to let is a function of the risk-free interest rate, the risk premium and a constant rate of growth of generated cash flows. In the article, five different elements of the risk premium were identified (term structure, alternative investments’, market (country) specific, monetary and local office market capacity risk premium). The Error Correction Model was formulated based on quarterly time series data from 2007Q1 to 2021Q2. Most investors in the office market in Poland are financial institutions representing foreign capital. Therefore, the innovation of the paper and its main goal was to define which factors play key roles in determining yield rates in the Warsaw office space market – national or regional/international. However, the selected group of Polish determinants were indicated as having prevailing an impact on the yield rate in the Warsaw office market than the corresponding determinants from the European Monetary Union and the USA. Based on the model, the lead-lag, as well as asymmetric relations, were depicted. Moreover, the use of dummy variables checks, the Chow test and the Markov switching model indicated the presence of structural breaks and the existence of the two regimes in the model.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 89-114